Evaluation of Faba Bean (Vicia faba L.) Varieties against Faba Bean Gall Disease in North Shewa Zone, Ethiopia - Wondwosen, Wulita; Dejene, Mashilla; Tadesse, Negussie; Ahmed, Seid (Review of Plant Studies, 2019)
Faba bean gall disease is a newly emerging and devastating disease of faba bean that threaten its production and productivity in Ethiopia. Thus, this study was conducted with the objective to evaluate the reactions of faba bean varieties against faba bean gall disease. A field experiment was conducted at Basona Werana and Ankober Districts, in 2014. Sixteen faba bean varieties along with local check were tested in RCBD design with three replications. Faba bean varieties varied significantly (p<0.05) for both disease and yield parameters. The lowest disease severity, AUDPC and infection rates were recorded from variety Gachena (Lay Gorebela) and Gora and Gachena (Mush). Moreover, the highest (2737 and 3374%-days) AUDPC values were recorded from the variety local and Selale at Mush and Lay Gorebela. The highest yield was obtained from varieties Gora, Gebelcho, Degaga, Gachena and Walki (Mush) and from varieties Gora and Gachena (Lay Gorebela). Also, yield of faba bean correlated negatively and significantly with AUDPC and final severity at both locations, whereas, AUDPC and severity associated positively and significantly from each other. From this study it can be concluded that relatively resistant and high yielder varieties can be used in combination with other control measures. Therefore, in the future, researches on integration of resistance and high yielder varieties with other management options should be conducted.